2022
DOI: 10.21037/tlcr-21-938
|View full text |Cite
|
Sign up to set email alerts
|

The predictive utility of patient-reported outcomes and performance status for survival in metastatic lung cancer patients treated with chemoimmunotherapy

Abstract: Background: Atezolizumab, an immune checkpoint inhibitor, in combination with chemotherapy (chemoimmunotherapy) has become a first-line treatment option for metastatic non-small cell lung cancer (NSCLC). Patient-reported outcomes (PROs) are self-reported measures that have shown promise in their predictive value for survival. However, there have been no studies that have assessed the prognostic performance of PROs in an advanced NSCLC cohort initiating first-line atezolizumab based chemoimmunotherapy.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Lastly, the present study highlights the relevance of understanding and appreciating information. Results suggest that general cognitive function abilities predict decision‐making capacity, 27 as supported by the biomedical literature 42,45 . Therefore, patients who show difficulties in understanding information could benefit from enhanced support, such as receiving information through multiple methods (e.g., hearing and seeing).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Lastly, the present study highlights the relevance of understanding and appreciating information. Results suggest that general cognitive function abilities predict decision‐making capacity, 27 as supported by the biomedical literature 42,45 . Therefore, patients who show difficulties in understanding information could benefit from enhanced support, such as receiving information through multiple methods (e.g., hearing and seeing).…”
Section: Discussionmentioning
confidence: 66%
“…Results suggest that general cognitive function abilities predict decision‐making capacity, 27 as supported by the biomedical literature. 42 , 45 Therefore, patients who show difficulties in understanding information could benefit from enhanced support, such as receiving information through multiple methods (e.g., hearing and seeing). Moreover, patients could be provided with summaries of information and enough time to paraphrase what was explained, reviewing information again with the physician.…”
Section: Discussionmentioning
confidence: 99%
“…The study covered patients at all stages of treatment, including those in advanced stages. Such patients have a poorer quality of life and more severe symptoms of fatigue as a result of multi-line treatment (29). A previous multicenter, large prospective cohort study showed that disease progression in cancer patients was signi cantly associated with a decline in quality of life, with the greatest impact on appetite, physical function, and fatigue (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, this index measures functional status but does not assess the cause, and as a result, very different patients may be categorized with the same PS. The ECOG PS scale is influenced by different aspects, such as the burden of the disease itself, the presence of comorbidities and the global frailty of elderly people [16].…”
Section: Introductionmentioning
confidence: 99%